(untitled) (Research, Society and Development, 2022)
The objective was to analyze the epidemiological profile of fetal deaths in Brazil, from 2015 to 2020. In this sense, the analysis was carried out using data taken from the Department of Informatics of the Unified Health System (DATASUS), in the section "Vital Statistics”, in the topic “Fetal deaths”. duration of pregnancy, birth weight and maternal education. The results showed the occurrence of 182,612 cases, with 2015 being the year with the highest occurrence with 32,994 (18.06%). (37.04%), followed by the Northeast region with 61,114 deaths (33.46%), totaling 70.5% of deaths. São Paulo was the most affected state with 31,817 cases. The occurrence of fetal deaths was more prevalent in baby’s male (52.11%), with a gestational age between 32 and 36 without anas and weight of 500-999g; with mothers aged 20-24 years, with 8 to 11 years of schooling, who underwent vaginal deliveries, being in a single pregnancy.